SOSIALISASI LITERASI PARAMETER KUALITAS AIR BERSIH BAGI MASYARAKAT DI DESA BALUKON - Toepak, Erwin Prasetya; Sambung, Roby; Kristinae, Vivy; Mahrita, Ani; Giovanni, Jonathan; Prakosos, Rian Sidiq; Bancin, John Budiman (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
The availability of clean water that meets quality standards is one of the main challenges in Balukon Village, where most people need to understand the importance of knowing the parameters of clean water quality. Socialization regarding water quality parameters is carried out to increase community literacy regarding this aspect. The method used involves direct explanations based on community participation through the delivery of materials that are relevant to everyday life. The results of the activity showed that there was community understanding of water quality parameters, such as pH, turbidity levels, and microbial content. Interactive discussions and simple but contextual delivery were the main factors in the success of this program. In conclusion, socialization based on direct education is effective in increasing clean water literacy at the community level. This program can be a model for implementation in other areas with similar conditions.